'Come, so that I may Chase you Away!' On Ghost Hunts and Posthuman Ethics. (March 2014) - Henriksen, Line
Abstract : 'Creepypastas' are short horror stories that circulate online, spreading through the act of copying and pasting, and often threatening to 'curse' the reader in the process. In this article I explore what it might mean to strike up companionship with and show responsibility towards that which is considered non-existent yet, as in the case of creepypasta and its monsters, hauntingly present nonetheless. I do so through the framework of Jacques Derrida's 'hauntology' as well as Donna Haraway's work on responsibility as a question of how to respond to the response of the non/human other. The question I would like to ask is this: how might one respond to the response of the non/human other, if the non/human other is considered to not exist?